Representation and delegation of powers. Political uses of mandate in the duchy of Burgundy (13th-14th centuries) - Torres Fauaz, Armando (2019)
This paper addresses the public uses of the roman-canonical legal technique known as mandatum, as it was effected in the duchy of Burgundy during the 13th and early 14th centuries. The main objective is to show how important this technique was for the delegation of powers and for political and judicial representation, both of which are essential to lay governance in the medieval West.